Bayesian optimization of proton generation in terawatt laser–CH2 cluster interactions within a plasma channel - Kim, Artem; Botton, Mordechai; Zigler, Arie (Frontiers in Physics, 2024)
Improving the energy efficiency in generating high-energy proton or boron ions is crucial for advancing the feasibility of neutronless laser-based proton-boron (p-B 11 ) fusion reaction. The primary objective of this work is to optimize the fusion energy efficiency of a proposed advanced p-B 11 fusion scheme. In the proposed scheme ultrashort laser pulse is guided by plasma channel filled with carbon-hydrogen (CH2) clusters. The MeV protons are generated by Coulomb explosion (CE) of the cluster, which therefore interact with surrounding boron to produce alpha particles. To evaluate the fusion energy efficiency under various conditions, 2D Particle-in-Cell (PIC) simulations are employed, supplemented with analytical calculations and estimations. The Bayesian optimization (BO) algorithm is utilized to optimize the key interaction parameters. The BO approach allows to identify optimal cluster and laser parameters that would have higher fusion energy efficiency.